Некоторые материалы к размножению карпатского глухаря (Tetrao urogallis L.) - Островский, А.И. (Вестник зоологии, 1973)
On the basis of long-term field investigations the distribution by biotopes and number dynamics are studied in Tetrao urogallus L. from the alpine areas of the Carpathians in the Ivano-Frankovsk region territory. Peculiar facts on ecology, in particular, on T. urogallus reproduction are presented. Recommendation are given for protection and increase of T. urogallus number in the Soviet Carpathians.